Civil Society Principles of Prophetic Era (622-632 AD): A Solution for Creating Harmonious Society in Indonesia - Namira Risqi Putri Muquita; Muhammad Irsyad Abiyusfi Ghafari (Millati: Journal of Islamic Studies and Humanities, 2021)
In the 13th years of prophecy, Prophet Muhammad PBUH along with 75 followers of him went to Yastrib, later turned to Medina City. The people of Yastrib who yearned for wise leader than asked Prophet Muhammad SAW to became their leader. Later, Prophet Muhammad PBUH established The Medina Charter which became the legal foundation for the governance in Yastrib. The Medina Charter confirmed the principles of the community such as tolerance, brotherhood, amr ma’ruf nahi munkar, equality, discussion, justice and balance. These principles became basic foundation in term of government and social affairs. This concept of civil society which built by Prophet Muhammad PBUH was relevant to the Indonesian society of which plural and grounded by kinship and mutual cooperation. The concept of civil society could make harmonious society in Indonesia and eliminated various irregularities and chaos within the governance or society. This could be done by SWOT analysis through minimalized the weaknesses and threats along with maximalized strengths and opportunities within Indonesian society.